An Integrative Model of Kyai Leadership in Building Islamic Education Management: A Systematic Literature Review - Suprihno Suprihno; Binti Maunah; Asrof Syafi’i (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to synthesize and analyze previous research findings on kyai leadership in building Islamic education management and to develop a conceptual model that explains the relationships among the various dimensions of kyai leadership. The study employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. The literature search was conducted through the Scopus database using keywords related to kyai leadership, transformational leadership, Islamic education, and Islamic education management. From an initial pool of 312 identified articles, 42 articles met the inclusion criteria and were subjected to an in-depth analysis using thematic synthesis techniques. The findings reveal that kyai leadership is a multidimensional phenomenon consisting of seven major dimensions: spiritual leadership, charismatic leadership, transformational leadership, visionary leadership, cultural broker leadership, entrepreneurial leadership, and adaptive-collaborative leadership. The study further demonstrates that kyai serve as spiritual leaders, agents of organizational change, developers of institutional culture, educational innovators, cultural mediators, community empowerment leaders, and managers of educational transformation. Based on the synthesis of the reviewed literature, this study proposes an Integrative Model of Kyai Leadership in Building Islamic Education Management, which incorporates these seven leadership dimensions into a unified conceptual framework. This study contributes theoretically to the advancement of Islamic education management literature and provides a foundation for future research on Islamic educational leadership.